1984
DOI: 10.3102/00346543054002143
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Problems of Beginning Teachers

Abstract: Perceived problems of beginning teachers in their first years of teaching are reviewed. Studies from different countries are included. Issues such as the reality shock and changes in behaviours and attitudes are considered also. The eight problems perceived most often are classroom discipline, motivating students, dealing with individual differences, assessing students’ work, relationships with parents, organization of class work, insufficient and/or inadequate teaching materials and supplies, and dealing with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

36
767
4
338

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,631 publications
(1,145 citation statements)
references
References 38 publications
36
767
4
338
Order By: Relevance
“…However, for novice teachers, those new beginnings might imply frustration and disappointment. As widely recognised and documented in the research literature, initial years of teaching have been marked with confusions, challenges and tensions (Farrell, 2003;Farrell, 2006;Loughran, Brown, & Doecke, 2001;Veenman, 1984). Research in educational literature has paid considerable attention to those challenges of first years of teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for novice teachers, those new beginnings might imply frustration and disappointment. As widely recognised and documented in the research literature, initial years of teaching have been marked with confusions, challenges and tensions (Farrell, 2003;Farrell, 2006;Loughran, Brown, & Doecke, 2001;Veenman, 1984). Research in educational literature has paid considerable attention to those challenges of first years of teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Research in educational literature has paid considerable attention to those challenges of first years of teaching. Veenman (1984), in his analysis of eighty-three studies, provided a comprehensive list of areas of difficulty as perceived by beginning elementary and secondary teachers. The reported problems covered such areas: classroom management, assessment, relations with parents, administrators, and colleagues, heavy teaching load, knowledge of subject matter and school rules, inadequate school materials, inadequate guidance and support, large class sizes.…”
Section: Introductionmentioning
confidence: 99%
“…However, possible problematic cases during practicum are inevitable. Veeman (1984) indicated that certain problems focused on three facets, i.e., student (e.g, dealing with problems of individual students), material (e.g, insufficient and/or inadequate teaching materials and supplies), and parents (e.g, unable to build positive relationships with parents). Additionally, Huang and Waxman (2009) identified that pre-service teachers perceived a large gap between expected ideal practicum situation and realistic practicum school environment when they engaged in field-based school experiences.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the fact that "the ideals that the beginning teacher formed during teacher training are replaced by the reality of school life where much of their energy is often transferred to learning how to survive in a new school culture" (Farrell, 2006, p. 212). Issues such as classroom discipline, dealing with individual differences and mixed-ability classes, organization of class work, relationships with parents, insufficient and/or inadequate teaching materials, overcrowded classrooms, sitting arrangement, noise, and social and cultural activities (Sariçoban, 2010;Veenman, 1984), to name a few, usually get in the way of teachers, especially in their initial years of teaching. In many settings, such issues tend to constitute real challenges that all teachers must learn to cope with.…”
Section: Introductionmentioning
confidence: 99%